Fenomena Kecanduan Penggunaan Gawai (Gadget) pada Kalangan Remaja Suku Bajo - Chaidirman Chaidirman; Diah Indriastuti; Narmi Narmi (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2019)
Background: Socially the use of devices causes teenagers to become less sociable. Many teenagers spend most of their time playing gadgets so they carry them wherever they go. This happens to the Bajo tribes who experience social changes that have an impact on their life patterns.Method: This study was a qualitative study with a phenomenological approach with the population in this study were the teenagers of the Bajo Tribe in Wakatobi Regency as many as 227 people and the number of samples was six adolescences Bajo Tribe. Using samples with a purposive sampling technique. For gathering the data, the investigator employed interview and observation guidelines, video recorder, and field note. The researchers used observation, interview and video recording in collecting the data and employed thematic analysis in data analysis. Results: The results of the research on these were three themes including namely the use of devices, addiction and socialization revealed that the use of devices requires costs for operations and excessive use of devices will have an impact on health where adolescents have a sense of dependence on devices that have attractive designs, and cause individual and indifferent attitudes. Discussion: The conclusion of this study is that adolescents begin to lose time for socializing due to the use of devices that are interested in the applications in it